EFFECT OF EXECUTIVE COMPENSATION, REPRESENTATIVES OF FEMALE CFO, INSTITUTIONAL OWNERSHIP AND COMPANY SIZES ON TAX AGRESSIVITY MEASURES - Fen, Shie; Riswandari, Ernie (Universitas Pamulang, 2019)
Tax revenue is the main source of Indonesia’s revenue. On the other side, tax payer consider tax as an expense that should be minimized because it can reduce economic ability of companies This is the reason why companies want to do same aggressive tax planning.The purpose of this research is to analyse the effect to executive compensation, CFOs female representation, institutional ownership, and firm size on tax aggressiveness. This research used 47 sample of manufacturing firms listed in Indonesian Stock Exchange for period on 2014-2016 that acquired by purposive sampling method. The method of research analysis was used multiple regression analysis.The result of this research showed that simultaneously, executive compensation, CFOs female representation, institutional ownership, and firm size has significant effect on tax aggressiveness. Partially, executive compensation has significant effect on tax aggressiveness. While the CFOs female representation, institutional ownership, and firm size has no significant effect on tax aggressiveness.The results of this research conclude that executive compensation is one of effective to minimize tax expense. On the other way, it indicates the larger amount of executive compensation will increase the level of tax aggressiveness. Keywords: Executive compensation, CFOs female representation, institutional ownership, firm size, tax aggressiveness.